Tinjauan Literatur Tentang Dampak SDGs Terhadap Karier Manajerial Perempuan - Shantya Viratama, Dwi Nurmatin; Tiatri, Sri; Afendi, Jelien; Hannandira, Rosa; Putriadi, Harvi Wahyu; Aprilia Putri, Sherly Amanda (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Gender equality has become an essential part of the Sustainable Development Goals (SDGs), particularly Goal 5, which emphasizes the empowerment of women in managerial sectors. In Indonesia, although there has been an increase in women's workforce participation, gender disparities persist, especially in managerial positions. This study aims to explore the impact of SDG policies in enhancing women’s participation and career promotion in managerial positions in Indonesia. Using a literature review method, the study collects and analyzes various academic sources and policy reports related to women. The results show that SDG policies, particularly Goal 5 on gender equality, play an important role in increasing women's participation in managerial positions by fostering an inclusive work environment. Training programs and work flexibility help eliminate barriers, strengthen women’s roles in decision-making, and contribute to both company performance and economic growth. Despite progress in increasing women's participation, significant challenges remain, such as wage gaps, gender stereotypes, and structural barriers that prevent women from reaching leadership positions. This study highlights the need for more effective strategies and collaboration between the government and private sector to address these obstacles and strengthen women’s roles in the workforce, in line with SDG 5, which emphasizes gender equality and women’s empowerment across all sectors.